(untitled) (JS (JURNAL SEKOLAH), 2023)
Abstract : The Effect Of The Time Token Learning Model In Theme 5, Subtheme 4 On Learning Outcomes Of Class II SDN 106798 Hamparan Perak. The purpose of this study was to determine the effect of the Cooperative learning model of the Time Token type on student learning outcomes in theme 5 sub-themes 4 class II SD Negeri 106798 Hamparan Perak in the academic year 2022/2023. This research is a Quasi experimental research with Pretest-Postest Nonequivalent Control Group Design by using total sampling as a sampling technique. The results of this study indicated that, the posttest results of students in the experimental class obtained an average of 81.43 and those in the control class obtained an average of 72.92. Thus, the comparison of the acquisition of the average student score looks different, namely 81.43> 72.92. Furthermore, the results of the hypothesis testing show that the acquisition of t_count > t_table = 2.934 > 2.017 with df = 43 at the sign level. (2-tailed) =0.025 (2.5%) is declared significant. Thus, it can be concluded that there is a significant influence of the time token cooperative learning model on student learning outcomes in class II SDN 106798 Hamparan Perak Keywords: Learning model cooperative type time token, Student Learning Outcomes Abstrak : Pengaruh Model Pembelajaran Time Token Pada Tema 5 Subtema 4 Terhadap Hasil Belajar Siswa Kelas II SDN 106798 Hamparan Perak. Tujuan penelitian ini adalah untuk mengetahui pengaruh model pembelajaran Cooperative tipe Time Token terhadap hasil belajar siswa pada tema 5 subtema 4 kelas II SD Negeri 106798 Hamparan Perak Tahun ajaran 2022/2023. Penelitian ini merupakan penelitian Quasi experiment dengan desain Pretest-Postest Nonequivalent Control Group Design dengan menggunakan teknik total sampling sebagai teknik pengambilan sampel. Hasil Penelitian ini menunjukkan bahwa hasil posttest siswa pada kelas eksperimen memperoleh rata-rata 81,43 dan pada kelas kontrol memperoleh rata-rata 72,92. Dengan demikian, perbandingan perolehan nilai rata-rata siswa terlihat berbeda yaitu 81,43 > 72,92. Selanjutnya, dilihat dari hasil uji hipotesis menunjukkan bahwa perolehan nilai > = 2,934 > 2,017 dengan df=43 pada taraf sign. (2-tailed) =0,025 (2,5%) dinyatakan signifikan. Dengan demikian, dapat disimpulkan bahwa ada pengaruh model pembelajaran cooperative tipe time token untuk hasil belajar siswa pada kelas II SDN 106798 Hamparan Perak Kata Kunci : Model Pembelajaran cooperative tipe time token, Hasil Belajar Siswa